2014
DOI: 10.1021/cg500816z
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Coprecipitation Method for the Controlled Synthesis of Magnetite Nanoparticles

Abstract: Nature often uses precursor phases for the controlled development of crystalline materials with welldefined morphologies and unusual properties. Mimicking such a strategy in in vitro model systems would potentially lead to the water-based, room-temperature synthesis of superior materials. In the case of magnetite (Fe 3 O 4 ), which in biology generally is formed through a ferrihydrite precursor, such approaches have remained largely unexplored. Here we report on a simple protocol that involves the slow copreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 43 publications
3
68
0
Order By: Relevance
“…Magnetite (Fe 3 O 4 ) is a biologically and technologically important magnetic iron oxide of which the magnetic properties depend on the size, shape, purity, and organization of the crystals . Magnetite biominerals encompass well‐defined, often single‐domain crystals as, e.g., encountered in the magnetosomes of magnetotactic bacteria, but also in the magnetoreceptive organs of migratory birds, honeybees,[5a], and certain fish.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) is a biologically and technologically important magnetic iron oxide of which the magnetic properties depend on the size, shape, purity, and organization of the crystals . Magnetite biominerals encompass well‐defined, often single‐domain crystals as, e.g., encountered in the magnetosomes of magnetotactic bacteria, but also in the magnetoreceptive organs of migratory birds, honeybees,[5a], and certain fish.…”
Section: Introductionmentioning
confidence: 99%
“…[295] Through this method, the controlled formation of ferrimagnetic magnetite with particle sizes up to 60 nm in the presence of Mms6 protein has closely mimicked the biomineralization process taken by MTB. It was suggested that Mms6 is a magnetite nucleation protein which binds iron ions specifically to nucleate the formation of magnetite.…”
Section: Protein Mediated Synthesis Of Magnetite Nanoparticlesmentioning
confidence: 98%
“…Cryo-TEM imaging is routinely chosen as a technique that does not require drying, thus allowing direct imaging of the features of interest [163,165]. When investigating the synthesis of magnetite, nanocrystals can be cryoplunged into liquefied ethane to arrest the nanoparticle growth at different stages of formation and obtain time-resolved information [7,[166][167][168][169]. HRTEM analysis has produced a wealth of knowledge about the iron oxide formation in biological and synthetic systems alike.…”
Section: The Near In Situ Approachmentioning
confidence: 99%
“…HRTEM analysis has produced a wealth of knowledge about the iron oxide formation in biological and synthetic systems alike. The "freeze and look" approach proved a very effective tool for evaluation of the complex synthetic pathways, notably the biomimetic formation of the nanoscale magnetite [165][166][167][168][170][171][172][173][174][175][176]. Importantly, the mechanism of biomimetic iron oxide formation remains unclear, largely because the analysis of the formed biomimetic solid is carried out either postsynthesis [6,21,22,34,44,78,177] or is performed on aliquots sampled during different stages of the growth process [165,166,171,173,[178][179][180][181][182].…”
Section: The Near In Situ Approachmentioning
confidence: 99%
See 1 more Smart Citation